Nilai-Nilai Etika dalam Anjuran Berbakti kepada Orang Tua: Studi Terhadap Hadits Rasulullah SAW - Muliyadi (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Parents, especially fathers and mothers, are central figures in a child's life who play a major role in the process of growth and character formation. From before birth to adulthood, children receive attention, affection, protection, and invaluable sacrifices from both parents. They carry out this noble duty wholeheartedly and without expecting anything in return, solely for the sake of their children's well-being and future. In this context, it is important for children to recognize the value of such sacrifices and cultivate a sense of devotion as a form of respect and gratitude. In Islamic teachings, the concept of devotion to parents is known as birrul walidain, which includes the obligation of children to treat their parents well, respect them, and pray for them. This study uses a qualitative method with a library research approach, aiming to explore and analyze Islamic values regarding children's obligations toward their parents based on relevant literary sources. The results of the study confirm that respect for parents is an integral part of character formation and noble values in Islam.